Contract pricing evaluation of distributed generation : a game theory approach (2012)
ABSTRACT: The main objective of this research is the contract pricing calculation of distributed generation (DG) considering its interaction with the distribution company. The proposed methodology consists in modeling the DGenergy trading using game theory concepts and bilevel programming. To validate the proposed methodology several tests are carried out with a 34 bus distribution system, changing the number and size of the DGunits. The contract prices calculated with this methodology represent an equilibrium between the profit maximization pursued by the DG owner and the minimization of payments procured by the distribution company. Consequently, it can be concluded that the proposed methodology provides efficient incentives for both agents, providing a solution in which the DGand the distribution company are mutually beneficial. Furthermore, the location of the DG units can also be considered in the model, so that not only the contract price but also the equilibrium location can be found.